Coated ternary positive electrode material, preparation method thereof and lithium ion battery
By covering the surface of the positive electrode material of lithium-ion battery, the problem of surface reconstruction and side reaction of lithium-ion battery under high pressure is solved, the cycle stability and fast charging and discharge capacity of the battery are improved, and high efficiency is achieved improves electrochemical performance.
Patent Information
- Application Number
- CN202411467559.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The surface reconstruction and side reaction of the existing lithium-ion battery positive electrode materials under high pressure lead to a degradation of cyclic performance, and the traditional modified coatings have poor bonding and insufficient stability, which affects the electrochemical performance.
The composite of graphene and WNb12O33 is used as the cladding layer, and the surface of the ternary positive electrode material is uniformly covered by the liquid phase coating method to improve the conductivity and crack resistance and reduce side reactions.
It significantly improves the migration rate of lithium ions and the fast charging and discharging capacity of lithium batteries, enhances cycle stability and structural stability, and has a simple process and low cost, which is suitable for large-scale production.
Smart Images

Figure CN119275274A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion battery materials, and specifically relates to a coated ternary positive electrode material, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] At present, lithium-ion batteries have been widely used due to their advantages such as high energy density, long cycle life, environmental friendliness, and rapid charge and discharge. As the positive electrode material of lithium-ion batteries, nickel-based layered oxides are considered to be one of the most promising materials. They have high energy density, but when they work under high voltage, the particle surface will be reconstructed, that is, irreversible phase change and increased side reactions with the electrolyte will occur, which will lead to a decrease in the cycle performance of the positive electrode material. Therefore, surface coating technology is often used to reduce the structural evolution of the surface of nickel-based ternary positive electrode material particles and direct contact with the electrolyte, thereby reducing the occurrence of side reactions on the particle surface and improving the service life of the positive electrode material.
[0003] Generally, the ideal modified coating on the surface of ternary cathode materials should not only have high electronic conductivity and ionic conductivity, but also have high chemical tolerance to electrolyte and strong mechanical strength to inhibit the cracking of cathode material particles. At present, traditional modified coatings are mostly metal oxides / fluorides, lithium conductors and conductive polymers, etc., and are coated on the surface of cathode materials by dry / wet method or physical / chemical vapor deposition method. However, the coatings coated by these methods have problems such as poor bonding with the cathode material matrix and uneven coating. In addition, the physical and chemical stability of traditional coatings is also poor, which will reduce the specific capacity of cathode materials and unbalance electrochemical stability.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present application is to provide a coated ternary positive electrode material, a preparation method thereof and a lithium-ion battery, aiming to coat the surface of the ternary positive electrode material with a stable modification layer with excellent physicochemical properties, so as to further improve the electrochemical performance of the lithium-ion battery.
[0006] In order to achieve the purpose of this application, this application adopts the following technical solutions: In the first aspect, the present application provides a coated ternary positive electrode material, the coated ternary positive electrode material comprising a substrate and a coating layer on the surface of the substrate; the substrate is a ternary positive electrode material LiNi x Co y Mn 1-x-y O 2 , wherein x>0, y>0, 1-xy>0; the coating layer is graphene and WNb 12 O 33 of the complex.
[0007] In an optional embodiment, the matrix of the coated ternary cathode material is LiNi x Co y Mn 1-x-y O 2 , where 1>x≥0.6, y>0, 1-xy>0.
[0008] In an optional embodiment, the mass percentage of carbon element in the coated ternary positive electrode material is 0.1%~0.4%, the mass percentage of tungsten element is 0.01%~0.05%, and the mass percentage of niobium element is 0.06%~0.3%.
[0009] In a second aspect, the present application provides a method for preparing a coated ternary cathode material, the preparation method comprising the following steps: Adding ternary cathode materials to the 12 O 33 The dispersion is heated and stirred until the solvent is evaporated to dryness to obtain a precursor; the precursor is subjected to a first sintering to obtain a coated ternary positive electrode material.
[0010] In an optional embodiment, the solvent in the dispersion is an ethanol aqueous solution, and the mass ratio of the ternary positive electrode material to the solvent is 1:(1-1.1).
[0011] In an optional embodiment, the heating temperature is 60-80°C.
[0012] In an optional embodiment, the temperature of the first sintering is 300-580° C., and the time of the first sintering is 7-9 hours.
[0013] In an optional embodiment, the ternary cathode material is obtained by mixing a ternary precursor with a lithium source and performing a second sintering.
[0014] In an optional embodiment, the ternary precursor is nickel cobalt manganese hydroxide Ni x Co y Mn 1-x-y (OH) 2 , where x>0, y>0, 1-xy>0.
[0015] In an optional embodiment, the ternary precursor is nickel cobalt manganese hydroxide Ni x Co y Mn 1-x-y (OH) 2 , wherein 1>x≥0.6, y>0, 1-xy>0, and the ratio of the total molar number of nickel, cobalt and manganese elements in the nickel, cobalt and manganese hydroxide to the molar number of lithium elements in the lithium source is 1:(1.02~1.05).
[0016] In an optional embodiment, the lithium source includes at least one of lithium nitrate, lithium chloride, lithium hydroxide or lithium carbonate.
[0017] In an optional embodiment, the temperature of the second sintering is 700-1050° C., and the time of the second sintering is 10-24 hours.
[0018] In an optional embodiment, the method for preparing the dispersion comprises: 3 and Nb 2 O 5 The mixture was ball milled at a molar ratio of 1:6 and sintered for the third time to obtain WNb 12 O 33 Nano oxide; dispersing graphene in an ethanol aqueous solution to obtain a graphene dispersion; WNb 12 O 33 The nano-oxide is dispersed in the graphene dispersion to obtain the dispersion.
[0019] In an optional embodiment, the ball milling speed is 400-600 r / min, and the ball milling time is 1-3 h.
[0020] In an optional embodiment, the temperature of the third sintering is 1050-1200° C., and the time of the third sintering is 6-12 hours.
[0021] In an optional embodiment, the volume ratio of ethanol to water in the ethanol aqueous solution is (3-4):1.
[0022] In an optional embodiment, the mass ratio of the graphene to the ethanol aqueous solution is (0.001-0.004):1.
[0023] In an optional embodiment, the WNb 12 O 33 The mass ratio of the nano-oxide to the ethanol aqueous solution is (0.001-0.005):1.
[0024] In a third aspect, the present application provides a positive electrode plate, wherein the positive electrode plate comprises the coated ternary positive electrode material as described in the first aspect.
[0025] In a fourth aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.
[0026] The present invention has the following beneficial effects: (1) The surface of the ternary cathode material of the present application is coated with graphene and WNb 12 O 33 The composite material, in which the flake graphene can not only12 O 33 Small particles are connected and stably attached to the surface of the positive electrode material, which can also improve the conductivity of the positive electrode material; WNb 12 O 33 NbO inside 6 Octahedron and WO 3 Tetrahedral, NbO 6 Octahedrons can form 3×4×∞ ReO by sharing corners. 3 Structural units, which can be connected to WO through shared edges 3 The shared corners of the tetrahedrons are connected to each other. This special structure can provide more isotropic Li + Diffusion tunneling, which in turn forms a clear conductive interface on the surface of the positive electrode material particles, further improves the migration rate of lithium ions in the positive electrode material and the rapid charging and discharging capabilities of the lithium battery.
[0027] (2) Graphene and WNb coated on the surface of the ternary cathode material of the present application 12 O 33 The composite layer has stable physical and chemical properties. It can not only effectively hinder the phase change on the surface of the positive electrode material particles and increase the crack resistance of the particles; it also has high corrosion resistance, which can effectively reduce the side reactions between the positive electrode material particles and the electrolyte, and further improve the cycle stability of the ternary positive electrode material.
[0028] (3) This application uses a liquid phase coating method to coat graphene and WNb 12 O 33 The composite is uniformly coated on the surface of the ternary positive electrode material. The preparation method has the advantages of simple process, low cost, environmental friendliness and easy large-scale production.
[0029] Other aspects will be apparent upon reading and understanding the drawings and detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are used to provide further understanding of the technical solution of this article and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of this article and do not constitute a limitation on the technical solution of this article.
[0031] Figure 1 This is a SEM image of the coated ternary cathode material prepared in Example 4; Figure 2 This is a SEM image of the ternary positive electrode material prepared in Comparative Example 1; Figure 3 This is the XRD diagram of the coated ternary positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0032] The technical solution of the present application is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present disclosure and should not be regarded as specific limitations of the present application.
[0033] It should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturers are not specified, are all conventional products that can be purchased commercially.
[0034] The technical terms "first", "second", etc. in this application are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0035] Reference to "embodiment" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.
[0036] The technical term "and / or" in this application is only a description of the association relationship between associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.
[0037] In addition, the character “ / ” in this application generally indicates that the preceding and following associated objects are in an “or” relationship.
[0038] In the present application, the meaning of “plurality” refers to more than two (including two), and the meaning of “at least one” refers to one or more than one.
[0039] In the first aspect, the present application provides a coated ternary positive electrode material, the coated ternary positive electrode material comprising a substrate and a coating layer on the surface of the substrate; the substrate is a ternary positive electrode material LiNi x Co y Mn 1-x-y O 2 , wherein x>0, y>0, 1-xy>0; the coating layer is graphene and WNb 12 O 33 of the complex.
[0040] In this application, a layer of graphene and WNb with stable physical and chemical properties is coated on the surface of the nickel-cobalt-manganese ternary positive electrode material. 12 O 33 Composite protective layer, in which graphene can improve the conductivity of the material, and WNb 12 O 33 The special structure can provide more Li+ The coating of the composite layer on the surface of the positive electrode material can not only reduce the direct contact between the material and the electrolyte and inhibit the occurrence of side reactions on the surface of the material, but also reduce the volume change of the material during charging and discharging, thereby improving its structural stability and cycle life.
[0041] In some embodiments, the coated ternary cathode material satisfies one or more of the following characteristics: Feature 1: The matrix of the coated ternary cathode material is LiNi x Co y Mn 1-x-y O 2 , where 1>x≥0.6, y>0, 1-xy>0; Feature 2: The mass percentage of carbon element in the coated ternary positive electrode material is 0.1%~0.4%, the mass percentage of tungsten element is 0.01%~0.05%, and the mass percentage of niobium element is 0.06%~0.3%.
[0042] The ternary cathode material with high nickel content can make the battery prepared by it have higher specific capacity and energy density. The cycle stability of the battery prepared by it can be further improved by surface coating modification of the high nickel ternary cathode material. 12 O 33 ) within an appropriate range can enable the ternary positive electrode material to obtain better electrochemical performance.
[0043] In a second aspect, the present application provides a method for preparing a coated ternary positive electrode material, the preparation method comprising: Adding ternary cathode materials to the 12 O 33 The dispersion is heated and stirred until the solvent is evaporated to dryness to obtain a precursor; the precursor is subjected to a first sintering to obtain a coated ternary positive electrode material.
[0044] This application adds ternary positive electrode materials to the 12 O 33 The dispersion is heated and sintered first. 12 O 33 It has a Wadsley-Roth crystal shear structure, which has the same parallel structure as the R-3m layer of the ternary cathode material in the
[100] direction. The similar crystal structure makes the WNb 12 O 33 It can grow along a specific direction on the surface of the ternary cathode material during the heat treatment process, thereby forming a uniformly coated graphene and WNb 12 O33 of composite layers.
[0045] In some embodiments, the heating temperature is 60-80°C, for example, 60°C, 70°C or 80°C, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0046] In some embodiments, the first sintering temperature is 300-580°C, such as 300°C, 380°C or 580°C, and the first sintering time is 7-9h, such as 7h, 8h or 9h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0047] In the present application, the first sintering temperature will affect the electrochemical properties of the ternary positive electrode material. If the sintering temperature is too low, the bonding strength between the composite layer and the positive electrode material will be low, thereby hindering the migration and diffusion of lithium ions; if the sintering temperature is too high, it will easily cause damage to the composite coating layer, thereby reducing the cycle performance of the positive electrode material.
[0048] In some embodiments, the ternary cathode material is prepared by mixing a ternary precursor with a lithium source and performing a second sintering.
[0049] In some embodiments, the ternary precursor is nickel cobalt manganese hydroxide Ni x Co y Mn 1-x-y (OH) 2 , where x>0, y>0, 1-xy>0.
[0050] In some embodiments, the ternary precursor is nickel cobalt manganese hydroxide Ni x Co y Mn 1-x-y (OH) 2 , wherein 1>x≥0.6, y>0, 1-xy>0, and the ratio of the total molar number of nickel, cobalt and manganese elements in the nickel, cobalt and manganese hydroxide to the molar number of lithium elements in the lithium source is 1:(1.02~1.05), for example, it can be 1:1.02, 1:1.04 or 1:1.05, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0051] In some embodiments, the second sintering temperature is 700-1050°C, such as 700°C, 800°C or 1050°C, and the second sintering time is 10-24h, such as 10h, 15h or 24h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0052] In some embodiments, the method for preparing the dispersion comprises: 3 and Nb 2 O 5 The mixture was ball milled at a molar ratio of 1:6 and sintered for the third time to obtain WNb 12 O 33 Nano oxide; dispersing graphene in an ethanol aqueous solution to obtain a graphene dispersion; WNb 12 O 33 The nano-oxide is dispersed in the graphene dispersion to obtain the dispersion.
[0053] The present application firstly prepares WNb 12 O 33 Nano oxides are dispersed in graphene dispersion, and under stirring, nano WNb 12 O 33 It can provide more active sites, allowing graphene nanosheets to adhere to its surface and fully penetrate into the WNb 12 O 33 The ternary cathode material is then mixed with graphene and WNb 12 O 33 The dispersion is mixed.
[0054] In some embodiments, the ball milling speed is 400-600 r / min, for example, 400 r / min, 500 r / min or 600 r / min, and the ball milling time is 1-3h, for example, 1h, 2h or 3h, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0055] In some embodiments, the temperature of the third sintering is 1050-1200°C, for example, 1050°C, 1100°C or 1200°C, and the time of the third sintering is 6-12h, for example, 6h, 8h or 12h, but not limited to the listed values, and other values not listed in the above numerical range are also applicable. In some embodiments, the graphene is dispersed in the ethanol aqueous solution under stirring conditions, and the stirring time is 25-50min, for example, 25min, 30min or 50min, but not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0056] In some embodiments, the mass ratio of the graphene to the ethanol aqueous solution is (0.001-0.004):1, for example, it can be 0.001:1, 0.002:1 or 0.004:1, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0057] In some embodiments, the WNb 12 O 33 The mass ratio of the nano-oxide to the ethanol aqueous solution is (0.001-0.005):1, for example, it can be 0.001:1, 0.002:1 or 0.005:1, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0058] In this application, graphene and WNb 12 O 33 The amount of the complex coated on the surface of the ternary positive electrode material will affect the electrochemical performance of the material. If the coating amount is too much, the composite layer on the surface of the material will be thicker, which is not conducive to the migration and transmission of lithium ions; if the coating amount is too little, the composite layer cannot be evenly coated on the surface of the material, and the contact between the positive electrode material and the electrolyte cannot be effectively isolated.
[0059] In a third aspect, the present application provides a positive electrode sheet, the positive electrode sheet comprising a coated ternary positive electrode material obtained in any of the above embodiments. The positive electrode sheet comprises a positive current collector and a positive active material layer, the positive active material layer comprising the coated ternary positive electrode material provided in the first aspect of the present application. A person skilled in the art may select a suitable method to prepare the positive electrode sheet, for example, the steps of: mixing the positive active material, the binder, and the conductive agent to form a slurry, and then coating it on the positive current collector.
[0060] In a fourth aspect, the present application provides a lithium-ion battery, comprising the coated ternary positive electrode material provided in the first aspect of the present application, or the positive electrode sheet provided in the third aspect of the present invention. The lithium-ion battery provided in the present application may generally include a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The method for preparing the lithium-ion battery should be known to those skilled in the art. For example, the positive electrode sheet, the separator, and the negative electrode sheet can each be a sheet body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium-ion battery.
[0061] Specifically, the features and performances of the present invention are further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0062] Example 1 This embodiment provides a method for preparing a coated ternary positive electrode material, the preparation method comprising: S1. Dissolve nickel sulfate, cobalt sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Co:Mn=90:5:5 to obtain 6L, 2mol / L transition metal sulfate solution; at the same time, obtain 7.2L, 2mol / L NH3 ·H 2 O and 5L, 5mol / L NaOH solution; a transition metal sulfate solution, ammonia water and sodium hydroxide solution with a flow rate of 0.3L / h are continuously injected into the intermittent reactor through a peristaltic pump to carry out a coprecipitation reaction, the reaction temperature is controlled to be 60°C, and the pH value of the reaction is maintained at 11.15 by controlling the flow rate of ammonia water and sodium hydroxide solution. Nitrogen is continuously introduced as a protective gas during the reaction. After the sulfate solution is completely injected into the reactor, all liquid inflows are stopped, and then the precipitate is allowed to stand for aging until the particle size Dv50 of the product particles is maintained in the range of 8.0-10.0μm, and then the product is filtered and washed with deionized water and anhydrous ethanol in succession, and finally the product is placed in a vacuum oven at 120°C for 18h to obtain a ternary positive electrode material precursor Ni 0.90 Co 0.05 Mn 0.05 (OH) 2 ; The ternary cathode material precursor Ni is prepared in a ratio of 1:1.04 based on the total molar number of nickel, cobalt and manganese elements to the molar number of lithium elements. 0.90 Co 0.05 Mn 0.05 (OH) 2 With LiOH·H 2 O was poured into a ball mill for mixing, the ball milling speed was controlled to be 150 r / min, the ball milling time was 6 h, and the mixed powder after ball milling was placed in a muffle furnace in an oxygen atmosphere at 800 ° C for 15 h. After the sintering was completed and cooled to room temperature, it was sieved with a 400 mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O 2 , denoted as NCM; S2, weigh 4.636g tungsten trioxide and 31.896g niobium pentoxide (WO 3 and Nb 2 O 5 The molar ratio of WNb was 1:6) and the ball milling speed was controlled to be 500 r / min and the ball milling time was 2 h. The mixed powder after ball milling was placed in a muffle furnace in air at 1100 ° C for 8 h to obtain WNb 12 O 33 Nano oxides; S3, 0.1g of graphene was dispersed in 100g of ethanol aqueous solution (V (ethanol): V (water) = 3:1), stirred for 30min to obtain a graphene dispersion; then 0.1g of WNb 12 O 33 The nano oxide is added to the graphene dispersion and stirred to obtain a graphene and WNb dispersion. 12 O 33A mixed dispersion of nano oxides; 100 g of ternary cathode material (NCM) was added to the mixed dispersion, heated and stirred at 70 ° C until the solvent was evaporated to dryness to obtain a precursor, and the precursor was placed in a muffle furnace in an oxygen atmosphere at 380 ° C for 8 h to obtain graphene and WNb 12 O 33 The composite-coated ternary cathode material. (The mass ratio of graphene to ethanol aqueous solution is 0.001:1, WNb 12 O 33 The mass ratio of ethanol to aqueous solution is 0.001:1) Example 2 The difference between this embodiment and embodiment 1 is that: S1, the same as step S1 of embodiment 1; In S2, the ball milling speed is 400 r / min and the ball milling time is 3 h; the mixed powder after ball milling is placed in a muffle furnace in air at 1200°C and sintered for 6 h; In S3, the mass ratio of graphene to ethanol aqueous solution is 0.002:1, and the stirring time is 25 min; WNb 12 O 33 The mass ratio of the precursor to the ethanol aqueous solution is 0.003:1; the solvent is heated and stirred until the temperature at which it evaporates is 60°C; the precursor is placed in a muffle furnace in an oxygen atmosphere and sintered at 580°C for 7 hours.
[0063] Example 3 The difference between this embodiment and embodiment 1 is that: S1, the same as step S1 of embodiment 1; In S2, the ball milling speed is 600 r / min and the ball milling time is 1 h. The mixed powder after ball milling is placed in a muffle furnace in air at 1050°C and sintered for 12 h. In S3, the mass ratio of graphene to ethanol aqueous solution is 0.004:1, and the stirring time is 50 min; WNb 12 O 33 The mass ratio of the precursor to the ethanol aqueous solution is 0.005:1; the solvent is heated and stirred until the temperature is 60°C for evaporation; the precursor is placed in a muffle furnace in an oxygen atmosphere at 300°C for 9 hours.
[0064] Example 4 The difference between this embodiment and embodiment 1 is that: S1-S2, the same as steps S1-S2 in Example 1; In S3, the mass ratio of graphene to ethanol aqueous solution is 0.002:1, WNb 12 O 33 The mass ratio of the ethanol solution to the aqueous solution is 0.002:1.
[0065] Example 5 The difference between this embodiment and embodiment 1 is that: S1-S2, the same as steps S1-S2 in Example 1; In S3, the mass ratio of graphene to ethanol aqueous solution is 0.003:1, WNb 12 O 33 The mass ratio of the ethanol solution to the aqueous solution is 0.003:1.
[0066] Example 6 The difference between this embodiment and embodiment 1 is that: S1-S2, the same as steps S1-S2 in Example 1; In S3, the precursor is placed in a muffle furnace in an oxygen atmosphere and sintered at 330° C. for 8 h.
[0067] Example 7 The difference between this embodiment and embodiment 1 is that: S1-S2, the same as steps S1-S2 in Example 1; In S3, the precursor is placed in a muffle furnace in an oxygen atmosphere and sintered at 500° C. for 8 h.
[0068] Comparative Example 1 Compared with Example 1, this comparative example prepares a ternary positive electrode material whose surface is not coated.
[0069] The difference between this comparative example and Example 1 is: In this comparative example, only step S1 of embodiment 1 is performed, and steps S2-S3 are not performed.
[0070] Comparative Example 2 Compared with Example 1, the surface of the prepared comparative example is coated with WO 3 and Nb 2 O 5 A mixture of ternary positive electrode materials.
[0071] The difference between this comparative example and Example 1 is: S1, the same as step S1 of embodiment 1; S2, weigh 100g of ternary cathode material (NCM), 0.025g of WO 3 and 0.175 g Nb 2 O 5 The precursor was evenly dispersed in 100 g of ethanol aqueous solution, heated and stirred at 70 ° C until the solvent evaporated to dryness, and the precursor was placed in a muffle furnace in an oxygen atmosphere at 380 ° C for 8 h to obtain a surface-coated WO 3 and Nb 2 O 5 Ternary cathode material.
[0072] Comparative Example 3 Compared with Example 1, this comparative example prepares a ternary positive electrode material whose surface is only coated with graphene.
[0073] The difference between this comparative example and Example 1 is: S1, the same as step S1 of embodiment 1; S2. Weigh 100 g of ternary positive electrode material (NCM) and 0.1 g of graphene respectively and evenly disperse them in 100 g of ethanol aqueous solution. Heat and stir at 70 °C until the solvent is evaporated to dryness to obtain a precursor. Place the precursor in a muffle furnace in an oxygen atmosphere at 380 °C and sinter for 8 h to obtain a ternary positive electrode material with graphene coated on the surface.
[0074] Comparative Example 4 Compared with Example 1, the surface of the comparative example is only coated with WNb 12 O 33 Ternary cathode material.
[0075] The difference between this comparative example and Example 1 is: S1-S2, the same as steps S1-S2 of embodiment 1; S3, weigh 100g of ternary cathode material (NCM), 0.1g of WNb 12 O 33 The precursor was uniformly dispersed in 100 g of ethanol aqueous solution, heated and stirred at 70 ° C until the solvent evaporated to dryness, and the precursor was placed in a muffle furnace in an oxygen atmosphere at 380 ° C for 8 h to obtain a WNb 12 O 33 Ternary cathode material.
[0076] Performance testing: 1. Particle size test The particle size of the coated ternary positive electrode material was tested using a GSL-101BI laser particle size analyzer.
[0077] 2. Electrochemical performance test 1) Preparation of button cells The coated ternary positive electrode material is homogenized in a mass ratio of positive electrode: conductive agent: binder = 80:10:10, the slurry is evenly coated on the electrode sheet, the electrode sheet is placed in an oven and dried at 80°C for 8h; after drying, it is punched into a circular positive electrode sheet and assembled into a button cell for electrochemical performance testing.
[0078] 2) Electrochemical performance test The electrochemical performance of the assembled button cell was tested in the charge and discharge voltage range of 2.8-4.3 V. The test results are shown in Table 1.
[0079] Table 1
[0080] In the attached figure: Figure 1 (ab) and Figure 2 The scanning electron microscope images of the ternary positive electrode materials prepared in Example 4 and Comparative Example 1 are shown in the figure. 12 O 33 The ternary cathode material coated with the composite layer ( Figure 1 a) The surface of the ternary cathode material without coating modification ( Figure 2 ) The surface is rough. Under a high-power microscope, it can be seen that the surface of the positive electrode material is evenly covered with dense granular substances ( Figure 1 b).
[0081] Figure 3 The XRD spectrum of the coated ternary positive electrode material prepared in Example 1 shows that the coated ternary positive electrode material in Example 1 has the same characteristic peaks as the standard card of lithium nickel cobalt manganese oxide, and has no other impurity diffraction peaks, indicating that graphene and WNb 12 O 33 The coating of the composite layer did not affect its phase structure.
[0082] From Table 1 we can see that: It can be seen from Examples 1-7 that the surface of the ternary positive electrode material prepared by the method described in this application is coated with graphene and WNb 12 O 33 The composite layer is prepared from the positive electrode material, and the lithium ion battery made from the positive electrode material has excellent cycle performance and fast charge and discharge capabilities.
[0083] By comparing Example 4 with Example 1 and Example 5, it can be seen that in the preparation process of the coated ternary positive electrode material described in this application, graphene and WNb 12 O 33 The amount of graphene used will affect the coating amount of the composite layer on the surface of the ternary cathode material, which will in turn affect the electrochemical performance of the cathode material. 12 O 33 If the mass ratio of graphene to ethanol aqueous solution is too low, the coating amount of the composite layer on the surface of the ternary cathode material is too small and the coating uniformity is poor, which will increase the side reaction between the electrolyte and the cathode material, thereby improving the cycle performance of the cathode material to a small extent; if the mass ratio of graphene to ethanol aqueous solution and WNb 12 O 33 If the mass ratio to the ethanol aqueous solution is too high, the composite layer will be coated too much on the surface of the ternary positive electrode material, and the composite coating will be thicker, which will hinder the migration and diffusion of lithium ions and further reduce the fast charge and discharge capability of the positive electrode material.
[0084] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the coated ternary positive electrode material described in the present application, the sintering temperature of the precursor product in step S3 will significantly affect the electrochemical properties of the material. If the sintering temperature is too low, the bonding strength between the composite and the positive electrode material is low, which will hinder the migration of lithium ions; if the sintering temperature is too high, it is easy to cause damage to the coating layer and thus reduce the cycle performance of the material.
[0085] By comparing Example 1 with Comparative Example 1, it can be seen that the surface of the ternary positive electrode material prepared in Comparative Example 1 has no coating layer. Compared with Comparative Example 1, the electrochemical performance of the lithium ion battery prepared by the positive electrode material of Example 1 is better. This is because the surface of the positive electrode material of Example 1 is coated with graphene and WNb 12 O 33 The composite layer has a high degree of bonding with the positive electrode material matrix and has stable physicochemical properties. The presence of the composite layer effectively avoids the dissolution of the active substance, and reduces the side reactions caused by the contact between the electrolyte and the positive electrode material, so it has good cycle stability and charge and discharge performance.
[0086] By comparing Example 1 with Comparative Examples 2-4, it can be seen that the surface coating layer of the ternary positive electrode material prepared in Comparative Example 2 is WO 3 and Nb 2 O 5 The surface of the ternary positive electrode material prepared in Comparative Example 3 is only coated with graphene, and the surface of the ternary positive electrode material prepared in Comparative Example 4 is only coated with nano-oxide WNb 12 O 33 , while the surface coating layer of the ternary cathode material prepared in Example 1 is graphene and WNb 12 O 33 Compared with Comparative Examples 2-4, the coating on the surface of the positive electrode material in Example 1 has a WNb 12 O 33 Highly conductive graphene nanosheets connected by particles and nano oxide WNb 12 O 33 NbO inside 6 Octahedron and WO 3 Tetrahedral, NbO 6 Octahedrons can form 3×4×∞ ReO by sharing corners. 3 Structural units, which can be connected to WO through shared edges 3 The shared corners of the tetrahedrons are connected to each other. This special structure can provide more isotropic Li + Diffusion tunneling is beneficial to improving the migration rate of lithium ions in the positive electrode material and the rapid charge and discharge capability of the lithium battery; the coating on the surface of the positive electrode material of Comparative Examples 2-4 does not have this structure, so the electrochemical performance of the lithium battery prepared therefrom is worse than that of Example 1.
[0087] The applicant declares that the above is only a specific implementation method of the present application, but the protection scope of the present application is not limited thereto. Technical personnel in the relevant technical field should understand that any changes or substitutions that can be easily thought of by technical personnel in the relevant technical field within the technical scope disclosed in the present application are within the protection scope and disclosure scope of the present application.
Claims
1. A coated ternary positive electrode material, characterized in that: The coated ternary positive electrode material comprises a substrate and a coating layer on the surface of the substrate; the substrate is a ternary positive electrode material LiNi x Co y Mn 1-x-y O2, wherein x>0, y>0, 1-xy>0; the coating layer is graphene and WNb 12 O 33 of the complex.
2. The coated ternary positive electrode material according to claim 1, characterized in that: The coated ternary cathode material meets one or more of the following characteristics: Feature 1: The matrix of the coated ternary cathode material is LiNi x Co y Mn 1-x-y O2, where 1>x≥0.6, y>0, 1-xy>0; Feature 2: The mass percentage of carbon element in the coated ternary positive electrode material is 0.1%~0.4%, the mass percentage of tungsten element is 0.01%~0.05%, and the mass percentage of niobium element is 0.06%~0.3%.
3. A method for preparing a coated ternary positive electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: Adding ternary cathode materials to the 12 O 33 The dispersion is heated and stirred until the solvent is evaporated to dryness to obtain a precursor; the precursor is subjected to a first sintering to obtain a coated ternary positive electrode material.
4. The method for preparing a coated ternary cathode material according to claim 3, characterized in that: The solvent in the dispersion is an ethanol aqueous solution, and the mass ratio of the ternary cathode material to the solvent is 1: (1-1.1); And / or, the heating temperature is 60-80°C; And / or, the temperature of the first sintering is 300-580° C., and the time of the first sintering is 7-9 hours.
5. The method for preparing the coated ternary cathode material according to claim 3, characterized in that: The ternary positive electrode material is prepared by mixing a ternary precursor with a lithium source and performing a second sintering.
6. The method for preparing a coated ternary cathode material according to claim 5, characterized in that: The ternary precursor is nickel-cobalt-manganese hydroxide Ni x Co y Mn 1-x-y (OH)2, where 1>x≥0.6, y>0, 1-xy>0; The ratio of the total molar number of nickel, cobalt and manganese elements in the nickel, cobalt and manganese hydroxide to the molar number of lithium elements in the lithium source is 1: (1.02-1.05); And / or, the lithium source includes at least one of lithium nitrate, lithium chloride, lithium hydroxide or lithium carbonate; And / or, the temperature of the second sintering is 700-1050° C., and the time of the second sintering is 10-24 hours.
7. The method for preparing a coated ternary cathode material according to claim 3, characterized in that: The preparation method of the dispersion comprises: mixing WO3 and Nb2O5 by ball milling at a molar ratio of 1:6, and obtaining WNb 12 O 33 Nano oxide; dispersing graphene in an ethanol aqueous solution to obtain a graphene dispersion; WNb 12 O 33 The nano-oxide is dispersed in the graphene dispersion to obtain the dispersion.
8. The method for preparing a coated ternary cathode material according to claim 7, characterized in that: The ball milling speed is 400-600 r / min, and the ball milling time is 1-3h; and / or, the third sintering temperature is 1050-1200°C, and the third sintering time is 6-12h; And / or, the volume ratio of ethanol to water in the ethanol aqueous solution is (3-4):1; And / or, the mass ratio of the graphene to the ethanol aqueous solution is (0.001-0.004): 1; And / or, the WNb 12 O 33 The mass ratio of the nano-oxide to the ethanol aqueous solution is (0.001-0.005):
1.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the coated ternary positive electrode material as described in any one of claims 1 to 2.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Lithium ion battery cathode material and non-aqueous electrolyte batterie
CN109244443A
Ternary positive electrode material, preparation method and application thereof
CN114094067A
Positive electrode active material and preparation method thereof, positive plate and battery
CN115050946A
Active electrode material
GB202008352D0
High-efficiency thermo-hygrostat using inverter compressor
KR102597140B1
Cited By
Lithium secondary battery, negative electrode of lithium secondary battery, negative electrode material, modified graphite negative electrode active material and preparation method of modified graphite negative electrode active material
CN121565821A
Lithium secondary battery and its negative electrode, negative electrode material, modified graphite negative electrode active material and preparation method
CN121565821B